Family Leadership Deficiency and Social Dysfunction in Isidore Okpewho’s The Victims - Ajogbor , Jimmy (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
With the reoccurrence of leadership failure and political instability in the African Society, the necessity for leadership accountability at the microcosm has called for attention. Consequently, this paper examines how leadership deficiency in the family unit, micro level of society, gives rise to social dysfunction at the macro or national realm. The study further evaluates families’ leadership deficit that has culminated in social crises. How such a deficit leads to social dysfunction is the goal of this examination. The adopted theory for this investigation is New Historicism with the core emphasis on the concept of power play while our primary data is drawn from Isidore Okpewho’s The Victims. To arrive at a result within the literary frame the study adopts an eclectic methodological approach of using a novel as data to assess the family unit as a political stratum in the strata of societal functionality. Our finding shows that deficient leaders and perpetrators of various societal vices in families or societies always lead to family or societal tragedy. Thus, condemning leadership deficiency and advocating for efficient leadership so that African society, particularly Nigeria, can experience steady growth and development.